Enhancing creativity for development of automation solutions using OTSM-TRIZ: A systematic case study in agronomic industry. (January 2018) - Nikulin, Christopher; Zuniga, Marcos; Akhloufi, Moulay; Manzi, Camila; Wiche, Christian; Piñones, Eduardo
The article describes a method to stimulate users' creativity within constraint-based scenarios and OTSM-TRIZ, which allows to define the problems and partial solutions to be solved during the design process in an appropriate manner. The proposed method aims to overcome constraints and problems defined within product development and related organization resources. Indeed, if these constraints are not properly taken into account, the risk of generating unsuccessful and even ineffective solutions can be high. In this work, a method has been defined, based on the OTSM-TRIZ theory: it guides the users toward the problem solution through a mapping of both the problem to solve and the relationships existing among the problems and constraints. A step-by-step approach is used to describe and propose a systematic structure, allowing to link the conceptual solution with specific solution criteria in the automation field. The validation of the proposed method corresponds to a real case study, that is, the necessity of increasing the productivity of an operational plant for the palletizing process has been selected to discuss the method implementation. Finally, the results of the case study were considered successful, because it was not necessary to introduce high investments for solution development and implementation.